THE EFFECT OF ORGANIZATIONAL CULTURE, NON FINANCIAL COMPENSATION AND JOB SATISFACTION ON ORGANIZATIONAL COMMITMENTS IN THE CENTER FOR STRATEGIC STUDIES OF TNI - Saputra Ridwan; Herminingsih Anik (Dinasti Publisher, 2020)
The purpose of this study was to determine the effect intended overall and partial between culture organizations, non-financial compenzation, job satisfaction and organizational commitment. Methods used in this research is by distributing questionnaires to employees is using a Likert scale, respondents who used as many as 55 employees, using SPSS 25 software programs, data analysis performed using validity, reliability and correlation of multiple linear regression. Sampling techniques were obtained from a sample of 55 respondents, data analysis techniques using multiple linear regression. The results showed that; (1) Cultural organizations significantly influence organizations commitment; (2) Non-Financial compenzaion significantly influence organizations commitment; (3) Job satisfaction significantly influence organizations commitment; (4) Organization culture and job satisfaction significantly influence organizations commitment